The Impact Of Problem Based Learning On The Students’ Learning Outcomes Toward Critical Thinking Skill In Elementary School - Agustiningsih Agustiningsih; Singgih Bektiarso; Arju Mutiah; Ahmad Ahmad (Pancaran Pendidikan, 2017)
Problem based learning supports students to have an ability to solve problems in real life, so that students’ critical thinking skill is structurally able to appear and is examined well. By problem based learning, students are able construct their own knowledges. This research is held in elementary school using true experimental with test post-test control group design. It uses quantitative descriptive approach. The data of critical thinking skill indicates that problem based learning does not affect significantly toward students’ critical thinking. The data of learning outcomes is analyzed by using t-test in 5 % signification level. The calculation result using t-test gains tcount = 2, 533. This value is consulted to ttable with db = 54 in 5 % signification level, so that it gains ttable = 2,005. It gains tcount>ttable (2,533 > 2,005). Based on its result, it can be concluded that problem based learning affects students’ learning result, unlike students’ critical thinking skill.